How service design can improve the patient experience - Rego, S.; Pereira, L.; Dias, Á.; Gonçalves, R.; Lopes da Costa, R. (International Journal of Services, Economics and Management, 2022)
Significant changes are taking place in healthcare organisations, where the pressure is increasing to develop personalised services that meet patients' needs while integrating the necessary resources. This research joins a stream of research that suggests that healthcare can be more patient-centred, where the role of the patient is redefined from passive recipient to more active and collaborative participant. Through the feedback of patients and health providers, the service design should improve service quality. It is essential first to identify the challenges in the service that need to be improved. The present study was developed according to answers given by patients and health providers from Portuguese cardiology units. Data were collected using two questionnaires. The main findings show that patient satisfaction is very high but can be improved through efficient management and digital innovation